Molecular environment and reactivity in gels and colloidal solutions under identical conditions. Issue 21 (20th May 2020) - Groves, Philip; Huang, Jin; Heise, Andreas; Marsh, Jennifer; Chechik, Victor
Abstract : PEG–Tyr block copolymers form gels and micelles that can co-exist under identical conditions. We compare molecular mobility and chemical reactivity in these two systems. Abstract : A PEG–Tyr block copolymer forms a kinetically stable colloidal solution in water at room temperature which undergoes an irreversible conversion to a gel phase upon heating. A micellar solution and a gel can therefore be studied under identical experimental conditions. This made it possible to compare physical properties and chemical reactivity of micelles and gels in identical chemical environments and under identical conditions. EPR spectra of the spin-labelled copolymer showed that tyrosine mobility in gels was slightly reduced compared to micelles. Chemical reactivity was studied using photochemical degradation of tyrosine and tyrosine dimerization, in the absence and in the presence of an Fe(iii ) salt. The reactivity trends were explained by reduced tyrosine mobility in the gel environment. The largest reactivity difference in gels and micelles was observed for bimolecular dityrosine formation which was also attributed to the reduction in molecular mobility.